Generation and Characterization of Closely Related Epizootic and Enzootic Infectious cDNA Clones for Studying Interferon Sensitivity and Emergence Mechanisms of Venezuelan Equine Encephalitis Virus - Anishchenko, Michael (American Society for Microbiology, 2004)
Venezuelan equine encephalitis virus (VEEV) is a reemerging pathogen and a continuing threat to humans and equines in the Americas. Identification of the genetic determinants that enable epizootic VEEV strains to arise and exploit equines as amplification hosts to cause widespread human disease is pivotal to understanding VEE emergence. The sensitivity to murine alpha/beta interferon-mediated antiviral activity was previously correlated to the epizootic phenotype of several VEEV strains. Infectious cDNA clones were generated from an epizootic subtype IC VEEV strain (SH3) isolated during the 1992 Venezuelan outbreak and a closely related enzootic, sympatric subtype ID strain (ZPC738). These VEEV strains had low-cell-culture-passage histories and differed by only 12 amino acids in the nonstructural and structural proteins. Rescued viruses showed similar growth kinetics to their parent viruses in several cell lines, and murine infections resulted in comparable viremia and disease. Unlike what was found in other studies of epizootic and enzootic VEEV strains, the sensitivities to murine alpha/beta interferon did not differ appreciably between these epizootic versus enzootic strains, calling into question the reliability of interferon sensitivity as a marker of epizootic potential.